Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content1. The Creative systems of the Arabesque and their use in silkscreen and stencil printingMrs. Walaa Mohamed Abdelaziz2. The features of Change in Land Usages Map at Alhanakiah City during the period from 1990-2020 using Remote Sensor TechnologiesDr. Shuded Ali Alharbi, Prof. Ahmed Mohammed Alshabaan3. The Eastern Coast of the Red Sea in Geographical Sources and the Moroccan and Andalusian Voyages between the two Centuries (4-6 AH / 10-12 AD) Using Geographic Information SystemsCo-Prof. Mona Salem Al-Harbi, Co-Prof. Wafa Zabin Al-Rehily4. The book (Almuhamashun in Islamic History) by Dr. Mahmoud Ismail in Al-MizanMr. Khalid Abdullah Alsaeed5. Challenges of using modern social media on the institution of the family in The Twenty-first century  – Descriptive study –Dr. Yusriya Ali Aman Al Jamil6. The effect of governance on development quality partnerships in the Ministry of Hajj and Umrah: a prospective study in 2022Dr. Raniah Khaled Aljohani7. (AL)’s Process from Mythology to LanguageMr. Motasim Basim Ghawadreh
Keywords: The Journal of Human and Social Sciences